Cracking Phenomena in Welds IV - Böllinghaus, Thomas; Lippold, John; Cross, Carl Edward (Springer International Publishing : Imprint: Springer, 2016)
This is the fourth volume in the well-established series of compendiums devoted to the subject of weld hot cracking.  It contains the papers presented at the 4th International Hot Cracking Workshop held in Berlin in April 2014. In the context of this workshop, the term "hot cracking" refers to elevated temperature cracking associated with either the weld metal or heat-affected zone. These hot cracking phenomena include weld solidification cracking, HAZ and weld metal liquation cracking, and ductility-dip cracking. The book is divided into three major sections based on material type; specifically aluminum alloys, steels, and nickel-base alloys.